PEMIKIRAN GENDER SACHIKO MURATA DAN RELEVANSINYA DENGAN FILSAFAT PENDIDIKAN ISLAM - riadil jannah, sitti (An - Nisa`, 2014)
The philosophical dimensions af Islamic education that ,relates closely effort of capacity human development to recognize the God recommends teachers to accommodate gender relation between male and female students established on similarity and justice. Accelarating the effort, Sachiko Murata offers cosmologic argument as well as theological one that can be an alternative reflection to see the gender relation in islamic education philosophy. The relevation between the philosophical dimensions of islamic education and Sachiko Muratas gender arguments can be an alternative effort to provide an islamic education philosophy that is gender-responsive.